PENERAPAN MODEL PjBL DALAM PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMA NEGERI 5 TERNATE - Ahmad, Rasno; Radjilun, Mus S (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
History education faces challenges of low learning outcomes, as indicated by suboptimal achievement scores, minimal participation, and a lack of commitment to completing assignments. These issues require teachers to design more engaging and interactive learning methods, such as the Project-Based Learning (PjBL) model. This study describes the implementation of the PjBL model in history education to enhance the learning outcomes of tenth-grade students at SMA Negeri 5 Ternate. This research is a classroom action research (CAR) study conducted at SMA Negeri 5 Ternate, involving 36 tenth-grade students as its subjects. The study followed CAR procedures, including planning, action, observation, and reflection. Data collection techniques included observation, tests, and documentation. Quantitative analysis was used to calculate student scores, while qualitative analysis compared test results and observations. The findings indicate that implementing the PjBL model successfully improved the history learning outcomes of Grade X students at SMA Negeri 5 Ternate. In Cycle I, 23 students achieved mastery, with an average score of 72.08 and a mastery percentage of 63.89%. Learning outcomes improved in Cycle II, with 34 students achieving mastery and an average score of 79.44, resulting in a mastery percentage of 94.44%. These results demonstrate that applying the PjBL model in history learning effectively enhances student learning outcomes.